2018
DOI: 10.1007/s00590-018-2127-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of modular megaprosthesis in managing chronic end-stage periprosthetic hip and knee infections: Is there an increase in relapse rate?

Abstract: According our data, MP is a useful tool in treating end-stage PJI cases, achieving acceptable eradication, satisfaction and implant survivorship rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
4
25
0
Order By: Relevance
“…Although a majority of patients in this study had improvement in limb functionality after two‐stage revision, the procedure was not without its complications. The most common complication following both megaspacer and megaprosthesis implantation was dislocation, which is similar to other studies evaluating outcomes after two‐stage revision 6,14,15 . We reported a total of six incidences of dislocation, of which five involved the hip.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Although a majority of patients in this study had improvement in limb functionality after two‐stage revision, the procedure was not without its complications. The most common complication following both megaspacer and megaprosthesis implantation was dislocation, which is similar to other studies evaluating outcomes after two‐stage revision 6,14,15 . We reported a total of six incidences of dislocation, of which five involved the hip.…”
Section: Discussionsupporting
confidence: 86%
“…We report on the surgical pathology and functionality of patients who undergo this procedure, which has not previously been documented. Another strength of our study relates to the severity of the cases included: no other study of megaspacers has reported on a cohort of PJI patients with such an extensive surgical history, persistence of infection despite prior spacer and antibiotic treatments, and high CCI as we describe here 5,6 . Additionally, all patients in our study were operated on by only two surgeons over the course of 3 years, which allowed for consistency in technique in contrast to Alvand et al 5 whose study consisted of 69 patients operated on by nine surgeons over the course of 7 years.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations